PENGGUNAAN METODE DISKUSI KELOMPOK PADA MATA PELAJARAN MATEMATIKA DAN PKN UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SDN 006 KOTO INUMAN KECAMATAN INUMAN - Aguswandi Aguswandi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
The background of this study is the low learning outcomes of mathematics and Civics students class V of SDN006 Koto Inuman Kecamatan Inuman. It can be seen from 17 students only 8 students (47,06%). On this basisresearchers do research by applying the method of discussion with the aim to improve learning outcomes. Thisresearch is a classroom action research conducted two cycles, each cycle is implemented based on four stages:planning, implementation, observation, and reflection. The result of research indicate that the result ofmathematics learning and student's Civic have improvement in each cycle, in cycle I the total number ofcomplete students is 13 students (76,47%) and in cycle II has increased with the total number of students is 17students (100 %). Based on the results of this study can be concluded that the application of discussion methodscan improve the learning outcomes of mathematics and Civics students class V of SDN 006 Koto InumanKecamatan Inuman.